Enhancing Biocrude and Hydrochar Production from Water Hyacinth via Hydrothermal Processing and Particle Flow Analysis - Aji Nugroho; Eka Dwi Ariyanto; Sudirman Rizki Ariyanto; Lailatus Sa’diyah Yuniar Arifianti; Shu-San Hsiau (JMES: The International Journal of Mechanical Engineering and Sciences, 2026)
This study investigates the hydrothermal conversion of water hyacinth (Eichhornia crassipes) into biocrude and hydrochar using a continuous stainless-steel reactor (2 L, 250-350◦C, 10-25 MPa). The effects of temperature, pressure, biomass-to-water ratio (1:3 to 1:10), and residence time (30-120 min) on product yield and quality were systematically examined. Particle dynamics and fluid flow within the reactor were analyzed using Computational Fluid Dynamics-Discrete Element Method (CFD-DEM) coupling, employing the Hertz-Mindlin contact model and Gidaspow drag law with a time step of 1 ×10−5 s. Results show that increasing temperature from 250◦C to 350◦C raised biocrude yield from 50 g to 70 g, while pressure increases (10-25 MPa) enhanced hydrochar yield from 30 g to 40 g. The optimal biomass-to-water ratio of 1:7 produced a hydrochar carbon content of 70%, and a residence time of 90 min maximized conversion efficiency at approximately 76.7%. CFD-DEM simulations revealed that higher pressures increased particle collision frequency, promoting biomass fragmentation and improving reaction surface area. These findings provide quantitative insights into optimizing hydrothermal reactor conditions for sustainable biomass conversion.